Small Yellow Ginger Juice Can be Used to Improve the Flavor and Quality of Jinjiang Oyster Meat During Enzymatic Hydrolysis Process - Yang, Zhao; Lin, Yijun; Liang, Yuyi; Chen, Xueren; Huang, Jiating; Cao, Dianxuan; He, Chunlan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Utilizing Jinjiang oyster in Guangdong Province as the research object, the effects of small yellow ginger juice on the color, taste, hydrolysis degree, and volatile components of oyster enzymatic hydrolysate (OEH) were investigated using sensory evaluation, NS810 colorimeter measurement, formaldehyde titration, Kjeldahl nitrogen determination, and headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS/MS). The results showed that OEH exhibited sea odor, earthy odor, and rancid flavor, which decreased with the increase in the amount of small yellow ginger juice, and were replaced by pleasant smells such as fruit, flower, and lemon. The optimal improvement in the quality of OEH was achieved with the addition of 8% small yellow ginger juice.